The Role of Aragwadha (Cassia fistula Linn.) Against Vata Rakta (Gout) - A Review - Sharma, Ish; Sharma, Chander Shekhar; Dhakad, Gagan Singh (International Research Journal of Ayurveda & Yoga, 2021)
The doctrine of Tridosha forms the cornerstone of Ayurveda , the oldest & pioneer healthcare / medical system in the world. The only difference between health and illness is the balance or imbalance among Tridosha . As per Ayurvedic literature, most of diseases arise of some imbalance of Jatharagni (Metabolism Process) .Vata Rakta / Gout is no exception, presenting with simultaneous imbalance among Vata, Rakta, and Agni. As per Ayurvedic therapeutic guidelines, this disease is be to be dealt with through Shaman & Shodhan modalilties . Gout is a prominent metabolic disorder, also featuring in the metabolic syndrome. Though much under rated, AAragwadhaa being mildly laxative/Mridu Virechak, anti dermatitis/Kandughna, anti-inflammatory /Jwarahar poses a huge potential as anti-Gout agent. These properties have been established by various modern researches as well.